2017
DOI: 10.1016/j.neulet.2017.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Vibration training after chronic spinal cord injury: Evidence for persistent segmental plasticity

Abstract: H-reflex paired-pulse depression is gradually lost within the first year post-SCI, a process believed to reflect reorganization of segmental interneurons after the loss of normal descending (cortical) inhibition. This reorganization co-varies in time with the development of involuntary spasms and spasticity. The purpose of this study is to determine whether long-term vibration training may initiate the return of H-reflex paired-pulse depression in individuals with chronic, complete SCI. Five men with SCI recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…In pathologies such as spinal cord injury (SCI), changes in H‐reflex behavior signify reorganization of spinal circuitry and may be germane to clinical syndromes such as spasticity . The normalization of H‐reflex behavior to a pre‐SCI pattern is a potential target for post‐SCI rehabilitation interventions . Understanding the conditions that modulate H‐reflex excitability in neurologically intact humans is an important foundation for the development of therapies for patients with neurologic pathology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In pathologies such as spinal cord injury (SCI), changes in H‐reflex behavior signify reorganization of spinal circuitry and may be germane to clinical syndromes such as spasticity . The normalization of H‐reflex behavior to a pre‐SCI pattern is a potential target for post‐SCI rehabilitation interventions . Understanding the conditions that modulate H‐reflex excitability in neurologically intact humans is an important foundation for the development of therapies for patients with neurologic pathology.…”
Section: Introductionmentioning
confidence: 99%
“…2 The normalization of H-reflex behavior to a pre-SCI pattern is a potential target for post-SCI rehabilitation interventions. 3,4 Understanding the conditions that modulate H-reflex excitability in neurologically intact humans is an important foundation for the development of therapies for patients with neurologic pathology.…”
Section: Introductionmentioning
confidence: 99%
“…After SCI, reorganization of spinal circuitry leads to loss of post activation depression (Ashby, Verrier, & Lightfoot, 1974; Calancie et al, 1993; Hiersemenzel, Curt, & Dietz, 2000; Schindler-Ivens & Shields, 2000; Shields, 2002; Skinner, Houle, Reese, Berry, & Garcia-Rill, 1996). We recently showed that constrained-limb vibration training can initiate a restoration of post-activation depression, even in patients with long-standing SCI (Yen, McHenry, Petrie, Dudley-Javoroski, & Shields, 2017). Vibration training may therefore have merit as an intervention to trigger neural adaptation in patients with SCI.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, compressive loading of limb segments fails to modulate PAD in SCI patients, revealing a decreased capability of spinal segment below the lesion to respond to short episodes of sensory stimulation [25]. However, an ever-growing body of evidence suggests that the reactivation of sensorimotor pathways for example by passive cycling movements, treadmill training, physical therapy or robotic-assisted gait training improve functional motor recovery and restore PAD expression in both humans and animals after SCI or stroke [20,[26][27][28]. The changes in PAD rate observed after motor mobilization requires the integrity of the sensory afferent pathways [29] and are accompanied by improvement in balance control [20].…”
mentioning
confidence: 99%
“…In this sense, TBS and STDP-like protocols appear to be highly valuable tools towards obtaining therapeutic benefits. In this context, it is noteworthy, that the data gathered on the PAD of H-reflex show that functional motor recovery is always associated with the restoration of a capability for synaptic plasticity (or vice versa) [20,[26][27][28]. Such findings lead to the chicken and egg dilemma.…”
mentioning
confidence: 99%